Management of Aggressive Pituitary Tumors – A 2019 Update - Petersenn, Stephan (Hormone and Metabolic Research, 2019)
With a prevalence of 80–100/100000, pituitary adenomas are more frequent than thought. The rare aggressive pituitary adenoma presents a special challenge, due to the heterogenous presentation of the disease. The prognosis of aggressive pituitary adenomas has been improved due to recent studies demonstrating some efficacy of chemotherapy with temozolomide. However, there is very limited data on second-line therapies in patients with treatment failure. This review presents an update on the diagnostic and therapeutic management of aggressive pituitary tumors. Patients should be treated by a team consisting of an expert endocrinologist, neurosurgeon, radiation oncologist, and pathologist, and according to the recently published ESE guideline.
Keywords: carcinoma; chemotherapy; temozolomide; PRRT; bevacizumab